2014
DOI: 10.3989/egeol.41753.325
|View full text |Cite
|
Sign up to set email alerts
|

Revisión de los modelos hidrogeoquímicos de génesis de tobas calcáreas

Abstract: RESUMENLos depósitos tobáceos en aguas dulces están ampliamente representados en la Península Ibérica, la mayoría de ellos relacionados con surgencias de acuíferos carbonáticos. Una gran parte de los modelos geoquímicos de la hidroquímica de las aguas en las que se generan dichos depósitos, se basan en suponer que el agua meteórica, previamente enriquecida en CO 2 por la existencia de actividad microbiológica en el suelo, fluye a través de la porosidad y de las fracturas de un acuífero de calizo. El agua resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recently, Ordoñez and Benavente () suggested that aquifers in dolomite and dolomite‐gypsum terrains may enhance the precipitation of tufa when dissolution of dolomite is congruent (i.e. dissolution of dolomite does not trigger precipitation of calcite as part of the reaction).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ordoñez and Benavente () suggested that aquifers in dolomite and dolomite‐gypsum terrains may enhance the precipitation of tufa when dissolution of dolomite is congruent (i.e. dissolution of dolomite does not trigger precipitation of calcite as part of the reaction).…”
Section: Discussionmentioning
confidence: 99%
“…Chong and Sheikholeslami, ; Ford and Williams, ; Brasier, ; Truedale, ). This implies that spring waters resulting from the mixing of sulphate and bicarbonate groundwater potentially enhance the precipitation of tufa compared to karst springs with only bicarbonate waters (Ordoñez and Benavente, ). Despite the importance of tufa deposits in karst landscapes, the scarce hydrological and hydrochemical description of tufa‐bearing springs at catchment scale prevents the confirmation of the previous hypothesis.…”
Section: Introductionmentioning
confidence: 99%